2022
DOI: 10.1177/11782234211065148
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features Related to the Efficacy of CDK4/6 Inhibitor-Based Treatments in Metastatic Breast Cancer

Abstract: Background: Resistance to endocrine therapy has been a major obstacle in the management of hormone receptor (HR)-positive metastatic breast cancer (MBC). Meanwhile, a number of treatments are available to such patients, and physicians often encounter difficulties in choosing the most appropriate treatments for individual patients. The combination of CDK 4/6 inhibitors (CDKi) and endocrine therapy has now become a standard treatment for HR-positive and human epidermal growth factor receptor 2 (HER2)-negative MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Our population is therefore notably homogeneous, that increasing the power. Indeed, other studies were interested in the NLR prognostic factor, but their population was inhomogeneous as they included patients at the localized and metastatic stage ( 39 ), or metastatic patients only and under cdk4/6 inhibitors but all lines combined without information on previous treatments ( 40 , 41 ). In this sense, it is an original study.…”
Section: Discussionmentioning
confidence: 99%
“…Our population is therefore notably homogeneous, that increasing the power. Indeed, other studies were interested in the NLR prognostic factor, but their population was inhomogeneous as they included patients at the localized and metastatic stage ( 39 ), or metastatic patients only and under cdk4/6 inhibitors but all lines combined without information on previous treatments ( 40 , 41 ). In this sense, it is an original study.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet-to-lymphocyte ratio (PLR) has also been studied, and for breast cancer patients, both NLR and PLR are now established prognostic markers across all intrinsic subtypes [ 10 , 12 , 13 ]. In relation to therapeutic effect, a high NLR reportedly correlates with poor responsiveness to systemic treatments in breast cancer patients [ 11 , 14 ] and we also previously reported a similar trend in eribulin-based and CDK4/6 inhibitor-based treatments [ 15 , 16 ]. Lymphocyte activity is also recognized as crucial and high lymphocyte counts are associated with better response to chemotherapies in patients with metastatic breast cancer [ 17 19 ].…”
Section: Introductionmentioning
confidence: 54%
“…Shikanai A and colleagues analyzed the clinicopathological features related to the efficacy of CDK4/6 inhibitor-based treatments in metastatic breast cancer in Japan [ 31 ]. They reported that progression-free survival (PFS) was significantly shorter in patients whose primary tumor was high grade ( p = 0.016) or in those with a high neutrophil-to-lymphocyte ratio (NLR) at baseline ( p = 0.017).…”
Section: Discussionmentioning
confidence: 99%